Synergy between Academics and the Community in the Development of Nagari Events: A CBR Study on the One Event One Nagari Program in Tanah Datar - Yuliani, Tri; Rikarno, Riki; Lani, Oktri Permata (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2025)
This community service initiative aims to strengthen collaboration between academic institutions and local communities through the Satu Event Satu Nagari (One Event One Village) program in Tanah Datar Regency. The primary objective is to empower nagari (villages) to independently plan and implement events that reflect their unique cultural identities and local potential. By doing so, the program fosters inclusive community development and promotes local tourism. Adopting a Community-Based Research (CBR) approach, the project emphasizes participatory methods and the co-production of knowledge between academics and community members. Implementation involves five key stages: 1) Initial community engagement and needs assessment, 2) Co-designing event concepts with community representatives, 3) Capacity building through workshops and training, 4) Pilot implementation of selected events, 5)Monitoring, reflection, and evaluation. The project has led to increased community involvement, enhanced capabilities among local organizers, and a strengthened sense of ownership over cultural heritage. Several nagari have successfully hosted distinctive events that drew local tourists and reinforced community cohesion. This model demonstrates strong potential for replication in other regions, contributing to the long-term sustainability of culturally grounded community development across West Sumatra.